1991
DOI: 10.1042/bj2780801
|View full text |Cite
|
Sign up to set email alerts
|

The importance of the negative charge of β-lactam compounds in the interactions with active-site serine dd-peptidases and β-lactamases

Abstract: The interaction between various penicillins and cephalosporins the carboxylate group of which at C-3 or C-4 had been esterified or amidated and different penicillin-recognizing enzymes was studied. In general, our findings reinforced the common assumption that an anionic group at that position is necessary for the effective acylation of these enzymes. However, the relative activities of the modified beta-lactams as inactivators of the Streptomyces R61 DD-peptidase or as substrates of the Bacillus licheniformis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 23 publications
4
33
0
Order By: Relevance
“…This neutral form would then be in place to act as a catalytic base, ultimately to the Tyr150 in deacylation but possibly also for acylation of Ser64 by a β-lactam substrate, as has been proposed by others. 10,26,38 This coordinate base hypothesis, though consistent with the ultrahigh-resolution structure on its own, is disfavored by previous biochemical experiments. Perhaps the strongest evidence against this hypothesis is the effect of the substitution Lys67→Arg, explored by Frère and colleagues.…”
Section: Discussionsupporting
confidence: 53%
“…This neutral form would then be in place to act as a catalytic base, ultimately to the Tyr150 in deacylation but possibly also for acylation of Ser64 by a β-lactam substrate, as has been proposed by others. 10,26,38 This coordinate base hypothesis, though consistent with the ultrahigh-resolution structure on its own, is disfavored by previous biochemical experiments. Perhaps the strongest evidence against this hypothesis is the effect of the substitution Lys67→Arg, explored by Frère and colleagues.…”
Section: Discussionsupporting
confidence: 53%
“…26,33 The energetic contribution of the primary carboxylate site of -lactams has only begun to be investigated for AmpC, but on the basis of studies of class A -lactamases, this site may contribute 3-4 orders of magnitude in binding affinity. 24,44,45 The contribution of the carbonyl/hydroxyl binding sites is not possible to estimate due to the covalent mechanism of the -lactams and the inability to uncouple the contributions of the hydroxyls from those of the boron in the boronic acids. Nevertheless, these binding sites appear to be regions of favorable energetic complementarity to AmpC.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of a quantum mechanics calculation study by Vaterro et al, however, the orientation of the C4-carboxyl group differed from that of the C3-carboxyl group of penicillins. 35) Moreover, structural analysis of the cepharoridineacylated double mutant (Glu166Asp:Asn170Gln) showed that the C4-carboxyl group made a weak hydrogen bond with Ser130O g (The C4-carboxyl oxygen-Ser130O g distance was found to be 3.78 Å.). 36) From these findings, the C4-carboxyl group seems to be inappropriate for a proton abstractor from the hydroxyl group of Ser130.…”
Section: Deacylation Mechanism Of Class a B-lacta-masementioning
confidence: 99%